Differences in the effects of resistance band and plank exercises on arm muscle endurance in archers at the blora archery club - Rachelino Wira Purnama; Pangestu, Arif; Frederico Rifqi; Lavaya Yuri Andjani; Danendra Luhung Saskara; Dhany Diva Pradana (Jorpres (Jurnal Olahraga Prestasi), 2025)
This study aims to determine the difference in the effects of resistance band and plank exercises on arm muscle endurance in archery athletes at the Blora Archery Club. The background of this study is based on the low variety of physical conditioning exercises and the weak arm muscle endurance of athletes, which affects their stability when shooting. The research method used is an experiment with a two-group pretest-posttest design. The research sample consisted of 12 archery athletes aged 13–17 years, who were divided into two groups using the ordinal pairing technique. The first group was given resistance band training, while the second group was given plank training for 16 sessions over a period of two months. The data collection instrument used was the Holding Bow Test. Data analysis was performed through normality tests, homogeneity tests, and paired sample t-tests. The results showed that both training methods had a significant effect on increasing the arm muscle endurance of archery athletes. However, plank exercises showed greater improvement than resistance band exercises, with correlation values of 0.938 and 0.876, respectively. Based on these results, it can be concluded that although both training methods are effective, plank exercises are superior in improving the arm muscle endurance of archery athletes. Therefore, it is recommended that coaches systematically combine both training methods to optimize athlete performance.